Keep calm and carry on? De toekomst van de sociaal-economische geschiedenis in de Lage Landen - Puttevils, Jeroen (TSEG - The Low Countries Journal of Social and Economic History, 2018)
This contribution offers a series of thoughts on new directions which social and economic history in the Low Countries might take. The field faces important challenges: source digitization, automatic handwriting recognition and digital methods of analysis. Somewhat ironically, social and economic history has received renewed interest after the 2008 financial and economic crisis. This crisis has fuelled research into inequality and capitalism and has forced economics as a discipline to question itself. One answer to the crisis of economics is to include more economic history. This essay emphasizes the fact that social and economic history is a house with many rooms and explicitly encourages social and economic historians to be inspired by other scholars, whether they be other historians or social scientists. One way to go forward might be the inclusion of insights from behavioral economics and the history of emotions which could lead to a fuller and more realistic analysis of the decisions individual historical actors took.